Dos tipos de libertad: lenguaje y práctica en las revueltas del último medievo (Edad Media. Revista de Historia, 2020)
This article looks at the role of freedom as a motivation for rural rebellion in northern Europe from c. 1200-1450. It focuses comparatively on the English Rising of 1381 and revolts in France with some further comparison to other regions. While discourses of freedom were important in 1381 both in the chronicle texts and to the rebels themselves, most rebels did not articulate their demands in terms of liberty. The last section demonstrates that although demands for freedom were rare in revolts, the social networks through which uprisings were organized show that rural communal practices constituted a kind freedom, enabling peasants to engage in socio-political action.
Keywords: English Rising (Peasants' Revolt); Jacquerie; Equality; Liberty; Serfdom